Participação social em saúde: percepção de moradores de uma comunidade - Delfim, Ana Magda Magnani (2016)
Brazilian health system (Sistema Único de Saúde - SUS) has, legally guaranteed, as one of its principle, participation of civil society in health councils and conferences - institutionalized participation - as guarantee that society are involved in the process of formulation and control of health policies. Equally important, is the non-institutionalized participation, which it consists in political performance of users daily based, social movements, popular movements, forums, social networks and collective existing in society. Taking into account that, society participation as producer of necessities to the life for their own players and adding to the fact that society and the processes that permeate the individual determine their health condition and welfare, becomes essential understand this context. Thus, understanding the social participation in health matters at a community ascribed to a Family Health Strategy team may contribute to studies of social sciences applied to health and development of a healthy society. This article is about a social research with qualitative research methodology of descriptive and analytical character, which the applied technique for primary data collection was semi-structured individual interview oriented by a guide. Participants of this article were people of the community from neighborhood Alonso Costa assisted at a Local Basic Health Unit ascribed to the team of ESF 031 in São José de Ribamar - Maranhão. Content analysis allowed knowing historical process and learning that trajectory of social participation at this community is marked by empowerment of community residents, with institutional support, guided by political and partisan interests, also by interest of people that live in the community and relationship with these people with health professionals. These factors have exerted a decisive role and conditioning factor for current decadence of the social movements at community. Yet, despite decades of praxis, social participation in formal spaces - institutionalized - is not known and/or is not accessible for most people and the non-institutionalized participation is surrounded by a number of factors that limit and discourage the community in the continuity of old social movements. Has identified as limiting factor of social participation in health the lack of information access and empowerment, nonexistence of a legitimate representative, distancing of institutionalized participation, poor involvement of health professionals with community, a not collaborative rivalry and the predominance of partisan politics logic, in addition to not solving basics necessities satisfactorily. It is still necessary to keep in mind that the process of empowerment for social participation in health matters reflects a collective daily effort that requires permanent investment "the" and "in" human capital.